Solid state fermentation and bioconversion of ripe and unripe pineapple peels using aspergillus Niger - Victor, Atere; Titilayo, Femi-Ola; Daniel, Fapohunda (International Journal of Scientific World, 2016)
Pineapple peels are considered as waste in industrial and house hold setting. This research was aimed at converting these waste into useful product through bioconversion using Aspergillus niger. The proximate analysis, reducing sugar, pH, and titratable acidity of the both ripe and unripe peels of pine apple was carried out at the onset of the fermentation and at an interval of 24 hours for 96 hours. These analyses carried out on both ripe and the unripe peels of pineapple showed that, the crude protein increased from 3.96% to 9.84% in the ripe pineapple peel and increased from 3.21% to 6.41% in unripe peels. The crude fiber reduced from 14.09% to 3.23% in the ripe pineapple peels while the crude fiber of the unripe peels reduced from 10.15 to 4.62 at the end of the 96 hour fermentation. Increase in titratable acidity, reduction in reducing sugar and pH was recorded for both ripe and unripe peels during the fermentation period. The optimum bioconversion was recorded at 72 hours of fermentation where the pick in the crude protein was recorded. The fat content of the pineapple peel in both ripe and unripe pineapple peel remain fairly constant throughout the fermentation period. The ripe pineapple peel yielded more protein compared to the unripe pineapple peels. This is an indication that the ripe pineapple peels are more preferred for industrial application.